La evolución de las prácticas de enseñanza/aprendizaje del léxico y del significado en los libros de texto de francés lengua extranjera - Delgado Guante, Denise (Anales de Filología Francesa, 2010)
We propose in this paper to analyze vocabulary teaching-learning practices and the access to word meanings in Second Language Acquisition. First of all, we will recount the evolution of didactic propositions concerning the methodological practices for vocabulary and meaning teaching practices during the last fifty years. Secondly, we suggest the study of four textbooks for French Second Language learners. We aim mainly to identify, on the one hand, which methodological conceptions are privileged in the vocabulary and meaning teaching-learning practices proposed in the textbooks and, on the other hand, how these practices are in line with approaches which take into consideration the learner and his communicative needs on second language.